FORMULASI DAN UJI MUTU FISIK LOTION DAUN TIN (Ficus carica L.) - novia ariani; Erna Fitriany (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2023)
Abstrack The fig plant is called fig in English. Most people often refer to it as a fig plant. This plant has the Latin name ficus carica L. The content of flavonoid compounds in the telang flower has the potential to be an alternative source of natural antioxidants. The purpose of this study was to determine the formulation and physical quality test of fig leaf extract lotion preparations. This research method is an experimental study of making fig leaf extract lotion by collecting the ingredients to be extracted using the maceration method with 70% ethanol solvent, formulating the extract concentration of 1%,3%,5% and evaluating the physical quality of the lotion preparation. The results obtained in the phytochemical screening are extracts containing flavonoid compounds, tannins and saponins. In the organoleptic test, homogeneity and pH have met the requirements and are safe to use for the skin.